Clinicopathological and Prognostic Significance of Stromal Patterns in Oral Squamous Cell Carcinoma - Amano, Yusuke; Kihara, Atsushi; Hasegawa, Masayo; Miura, Tamaki; Matsubara, Daisuke; Fukushima, Noriyoshi; Nishino, Hiroshi; Mori, Yoshiyuki; Niki, Toshiro (Frontiers in Medicine, 2022)
Background Stromal patterns (SP), especially desmoplastic reactions, have recently gained attention as indicators of malignant potential in cancer. In this study, we explored the clinicopathological and prognostic significance of the SP in oral squamous cell carcinoma (OSCC). Materials and Methods We reviewed 232 cases of surgically resected OSCC that were not treated with neoadjuvant chemoradiotherapy. We categorized the SP of the OSCC into four groups: immune/inflammatory (84 cases), mature (14 cases), intermediate (78 cases), or immature (56 cases). Results The SP category was significantly associated with various clinicopathological factors, such as the histological grade, lymphovascular invasion, neural invasion, and a diffuse invasion pattern. For each of the factors, the immune/inflammatory type was associated with favorable categories, while the immature type was associated with unfavorable categories (p ≤ 0.001). The SP category was also shown to be a prognostic predictor: the 5-year relapse-free survival (RFS) rate was 72.0% for the immune/inflammatory type, 66.7% for the intermediate/mature type, and 31.2% for the immature type (p < 0.0001), and the 5-year overall survival (OS) rate was 85.1% for the immune/inflammatory type, 76.4% for the intermediate/mature type, and 50.0% for the immature type (p < 0.0001). In multivariate analyses, the SP category was identified as an independent prognostic factor for RFS and OS. Conclusion Our SP categorization method provides valuable prognostic information in OSCC.